Respuesta :
Answer:
13
Step-by-step explanation:
To find the value of y, we will use the substitution method
Plug the y of the top equation into the other equation
2(5x + 3) = 18x - 10
Distribute the 2 into the equation inside the parenthesis
10x + 6 = 18x - 10
Subtract 10x from both sides
10x + 6 = 18x - 10
-10x -10x
6 = 8x - 10
Add 10 to both sides
6 = 8x - 10
+10 + 10
16 = 8x
Divide both sides by 8
16/8 = 8x/8
x = 2
Sub the 2 in the place of x into one of the original equations. We will use the first one.
y = 5(2) + 3
y= 10 + 3
y = 13
Answer:
y = 13
Step-by-step explanation:
y = 5x + 3
2y = 18x- 10
substitution (substituting y with the y value given):
2( 5x + 3 ) = 18x - 10
solve:
10x + 6 = 18x - 10
10x - 18x = -10 - 6
-8x = -16
x = 2
now plug in the x:
y = 5( 2) + 3
y = 10 + 3
y = 13